2010
DOI: 10.2337/dc10-0693
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Maternal Circulating Fatty Acid Composition and Dietary Fat Intake in Women With Gestational Diabetes Mellitus or Mild Gestational Hyperglycemia

Abstract: OBJECTIVEWe investigated the relationship between maternal circulating fatty acids (FAs) and dietary FA intake in pregnant women with gestational diabetes mellitus (GDM; n = 49), women with hyperglycemia less severe than GDM (impaired glucose challenge test [GCT] non-GDM; n = 80), and normal control subjects (n = 98).RESEARCH DESIGN AND METHODSA case-control design was nested within a prospective cohort of healthy pregnant women. Fasting concentrations of serum total FAs (enzymatic assay) and FA composition (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 22 publications
6
112
5
Order By: Relevance
“…Third, studies used different diagnostic criteria for GDM, with no clear pattern emerging regarding whether a significant association could be detected using less or more strict criteria. Some studies showed a gradient in dietary intake (e.g., increasing dietary fat intake) from normal glucose tolerance to abnormal glucose tolerance and GDM (39)(40)(41), whereas other studies found an association or no association consistent with both outcomes (16,20,42). Finally, the observed associations may be explained by residual confounding from unmeasured factors in the individual studies.…”
Section: Discussionmentioning
confidence: 96%
“…Third, studies used different diagnostic criteria for GDM, with no clear pattern emerging regarding whether a significant association could be detected using less or more strict criteria. Some studies showed a gradient in dietary intake (e.g., increasing dietary fat intake) from normal glucose tolerance to abnormal glucose tolerance and GDM (39)(40)(41), whereas other studies found an association or no association consistent with both outcomes (16,20,42). Finally, the observed associations may be explained by residual confounding from unmeasured factors in the individual studies.…”
Section: Discussionmentioning
confidence: 96%
“…The ewe is a well-established model for studying these mechanisms [31,32]. OA is a major component of NEFAs with evidence to suggest that concentrations of OA are elevated in women with obesity and that this may contribute to complications such as pre-eclampsia and premature delivery [3,6,9]. On the other hand, OA supplementation is credited with beneficial actions on neutralising the negative effects of dietary saturated fatty acids [14,33].…”
Section: Discussionmentioning
confidence: 99%
“…Women with non-esterified fatty acids (NEFA) levels in the highest tertile were at about twice the risk of spontaneous pre-term birth than those in the lowest tertile [3]. Amongst these, oleic acid (OA, 18:1n-9) accounts for about 30% of the NEFAs circulating during pregnancy in women and up to 45% in sheep [8]: its concentration increases in women with gestational diabetes mellitus [9] and OA was the NEFA with the greatest increase (67%) associated with pre-eclampsia [6]. OA also constituted around 10% of the fatty acids present in amniotic fluid [10] and 30% of total membrane fatty acids in immortalised pregnant human myometrial cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…These authors also compared fasting free fatty acid concentrations, and they found a significant difference (0.40 ± 0.33 vs. 0.52 ± 0.34, respectively, p = 0.02) [41]. Similarly, found maternal serum total fatty acids to be elevated in women with GDM when compared to controls [45]. In a study that used the data from the HAPO study, Scholtens et al (2014) showed that amino acid degradation pathways were altered in women with high FPG (>90th percentile) compared to women with low FPG (<10th percentile) at gestational weeks 24-32.…”
Section: Resultsmentioning
confidence: 89%
“…The metabolites most consistently associated with GDM were asymmetric dimethylarginine (ADMA) and NEFAs (major components of triacylglycerols) [25]. The latter have been found to be elevated in the third trimester of pregnancy [24,[39][40][41]. The inconsistency between the studies arose because they varied in several aspects, including the timing of serum sampling (early, mid, or late gestation), number of participants, fasting status, selection of metabolites, and differing glycemic control or treatment.…”
Section: Resultsmentioning
confidence: 99%